Volume 2B: Structures, Safety and Reliability 2013
DOI: 10.1115/omae2013-10820
|View full text |Cite
|
Sign up to set email alerts
|

Physical Component Testing to Simulate Dynamic Marine Load Conditions

Abstract: The reliability and integrity of components used in the marine offshore environment is paramount for the safety and viability of offshore installations. The engineering challenge is to design components that are robust enough to meet reliability targets whilst lean enough to minimise cost. This is particularly the case for offshore marine renewable installations which operate in the same, possibly harsher, environment as offshore oil and gas installations, and are subjected to highly cyclic and dynamic wave, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…less than 14% MBL) lower stiness values were reported for aged 8-strand plaited ropes in [6]. In the current study the trend of increasing axial stiness with the application of higher mean load levels is noted for both new and aged samples (Figure 7a), as observed in other studies [16,24,44,47]. A single degree-of-freedom line tted to mean load and axial stiness values (both normalised by the rope MBL) can be used to quantify the dynamic stiness of a sample [7].…”
Section: Measurement Analysis Proceduressupporting
confidence: 88%
See 1 more Smart Citation
“…less than 14% MBL) lower stiness values were reported for aged 8-strand plaited ropes in [6]. In the current study the trend of increasing axial stiness with the application of higher mean load levels is noted for both new and aged samples (Figure 7a), as observed in other studies [16,24,44,47]. A single degree-of-freedom line tted to mean load and axial stiness values (both normalised by the rope MBL) can be used to quantify the dynamic stiness of a sample [7].…”
Section: Measurement Analysis Proceduressupporting
confidence: 88%
“…For this study a 4.5m long sample was taken from the SWMTF rope with the original splice and eye retained at one end and three u-bolts used to terminate the other end. A second sample was taken from the SWMTF rope and used for preliminary tests at L'Institut français de recherche pour l'exploitation de la mer (IFREMER) and the University of Exeter [44]. Yarn assemblies, yarns and bres were extracted from the remaining central portion of the SWMTF rope for detailed analysis and testing.…”
Section: Rope and Yarn Samples And The South West Mooring Test Facilimentioning
confidence: 99%
“…It was also shown in [20] that there was an e ect of harmonic oscillation period (and hence load rate) on both average axial sti ness and damping. The axial sti ness values calculated for the bedding-in cycles contained within load sets LS1 and LS2 are in agreement with this, in that the lower axial sti ness values correspond to bedding-in cycles with lower load rates (Figure 6b).…”
Section: In Uence Of Load Ratementioning
confidence: 99%
“…Previous tests conducted by the authors on a section of aged rope of the same construction demonstrated that the application of higher mean load levels resulted in steeper hysteresis loops, leading to higher average axial sti ness values [20], re ecting studies conducted on HMPE and aramid ropes [6,11]. For load sets LS1 and LS2 the same e ect is demonstrated with the samples subjected to bedding-in cycles (Samples 2 and 3, subjected to BI2 and BI3 respectively) compared to Sample 1 (Figure 6a).…”
Section: Axial Sti Ness and Damping Performance 321 In Uence Of Mementioning
confidence: 99%
“…Performance and survival in extreme sea states 4. Indication of fatigue performance All tests have been carried on the Dynamic Marine Component test rig (DMaC), a unique facility to replicate the forces and motions that components and sub-systems are subjected to in (floating) marine applications [23][24][25]. It comprises of two hinged gimbles with a backplate, termed 'moving headstock' which is capable to replicate motions in 3°of freedom and a linear actuator to provide the axial loading on the specimen.…”
Section: Experimental Set-up and Proceduresmentioning
confidence: 99%